Molecular focus in p63 and correlated human diseases - Hashemi, Mehrdad; Jamshidian, Faranak; Shamei, Mohammad hassan (Archives of Advances in Biosciences, 2012)
The p63 gene, a member of the p53 gene family, is expressed into at least six protein isoforms.The transcription factor p63 is a homologue of the tumor suppressor p53. Unlike p53, which is dispensable for normal development, p63 is critical for the development of stratified epithelial tissues such as epidermis, breast, and prostate. p63, , is transcribed from two different promoters giving rise to two different proteins: p63, a member of the p53 family, is transcribed from two different promoters giving rise to two different proteins: TAp63 that contains the N-terminal transactivation domain and ΔN that lacks this domain. p63 encodes multiple protein isoforms with both transactivating and transcriptional repressor activities that can regulate a wide spectrum of target genes. p63 is also implicated in tumor formation and progression in stratified epithelia, with evidence for both tumor suppressive and oncogenic properties.